PENGARUH CAR, LDR DAN BOPO TERHADAP KINERJA PROFITABILITAS PADA SEKTOR PERBANKAN YANG GO PUBLIK DI BURSA EFEK INDONESIA TAHUN 2007 - 2010 (Students' Journal of Accounting and Banking, 2012)
This study aims to determine and analyze the influence of the CAR, LDR, and BOPO of the performance of banking profitability for the company go public in Indonesia with the observation period of 2007-2010. Important for the Bank's profitability because profitability is used to measure the effectiveness of the company in generating profits by leveraging its assets. Financial ratios that affect the profitability (ROA) are: CAR, LDR and BOPO.The population in this study is a commercial bank in Indonesia which went public in 2007-the period of study 2010.sampel taken by using purposive sampling so that the amount of observational data obtained in this study as much as 96 observational data from 24 sample banking firms each year.By using a multiple linear regression analysis, the results showed that the CAR shown to have a positive significant effect on ROA and BOPO significant negative effect on ROA while the LDR does not affect eye out ROA.Keywords: CAR, LDR, BOPO, ROA